2018
DOI: 10.1096/fj.201800988r
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity impairs fetal cardiomyocyte contractile function in sheep

Abstract: Obesity is a major public health problem worldwide. In the United States, one‐third of women of reproductive age are obese. Human studies show that maternal obesity (MO) predisposes offspring to cardiovascular disease. However, the underlying mechanisms remain unclear. Given the similarities between pregnancy in sheep and humans, we studied sheep to examine the impact of MO on fetal cardiomyocyte contractility at term. We observed that MO impaired cardiomyocyte contractility by reducing peak shortening and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 106 publications
1
30
0
Order By: Relevance
“…Huang et al indicated that maternal obesity results in greater fetal heart connective tissue accumulation associated with an upregulated TGF- β /p38 signaling pathway at late gestation, and such changes may negatively impact offspring heart function [67]. Secondly, it was reported that maternal obesity may impair fetal cardiomyocyte contractility and affect cardiac development by altering intracellular Ca 2+ treatment, overloading fetal Ca 2+ , and abnormal myofibrillar proteins [68]. Thirdly, maternal obesity significantly enhances TLR4, IL-1a, IL-1b, and IL-6 expression, promotes phosphorylation of I- κ B, decreases cytoplasmic NF- κ B levels, and increases neutrophil and monocyte infiltration, eventually leading to inflammation in the fetal heart and altering fetal cardiac morphometry [69].…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al indicated that maternal obesity results in greater fetal heart connective tissue accumulation associated with an upregulated TGF- β /p38 signaling pathway at late gestation, and such changes may negatively impact offspring heart function [67]. Secondly, it was reported that maternal obesity may impair fetal cardiomyocyte contractility and affect cardiac development by altering intracellular Ca 2+ treatment, overloading fetal Ca 2+ , and abnormal myofibrillar proteins [68]. Thirdly, maternal obesity significantly enhances TLR4, IL-1a, IL-1b, and IL-6 expression, promotes phosphorylation of I- κ B, decreases cytoplasmic NF- κ B levels, and increases neutrophil and monocyte infiltration, eventually leading to inflammation in the fetal heart and altering fetal cardiac morphometry [69].…”
Section: Discussionmentioning
confidence: 99%
“…60 In vitro function of isolated cardiomyocytes in foetuses of obese sheep showed impaired cardiomyocyte contractility through altered intracellular Ca 2+ handling, overloading of foetal cardiomyocyte intracellular Ca 2+, and aberrant myofilament protein composition. 61 In summary, the intrauterine environment can directly influence the health status by changing the structural development of the organs, altering cell number and maturation. However, foetal programming may result from cellular alterations that can predispose to disease later in life.…”
Section: Maternal Glucose Metabolism and Influence On Foetal Organs Growthmentioning
confidence: 99%
“…The MyoPacer frequency setting for cardiomyocyte contractility measurement was 1 Hz, with a stimulation pulse duration of 3 ms, at the voltage of 15 V. The cardiomyocyte being measured was displayed on the computer monitor via a MyoCam‐S (IonOptix) digital acquisition camera, and the amplitude and velocities of shortening and relengthening were recorded. Cell shortening and relengthening were assessed by using the following indices: peak shortening (PS), the shortest sarcomere length of cardiomyocytes contracted on electrical stimulation, which is indicative of peak ventricular contractility; time‐to‐PS (TPS), the duration of myocyte shortening, which is indicative of contraction duration; time to 50% relengthening (TR 50 ), the time to reach 50% relengthening, which represents cardiomyocyte relaxation duration (50% rather than 100% relengthening was used to avoid the noisy signal present at baseline contraction); and maximum velocities of shortening (+dl/dt) and relengthening (−dl/dt), maximum slope (derivative) of the shortening and relengthening phases, which are indicators of maximum velocities of ventricular pressure increase and decrease (Wang et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%